Improving Paragraph Writing Ability of the Fourth Semester Students of the English Department of Palangka Raya State Islamic College Through Cooperative Learning Strategy - Sabarun, Sabarun (Jurnal Studi Agama dan Masyarakat, 2009)
The objective of the study is to improve the studentsâ writing ability in writing English class by using Cooperative Integrated Reading and Composition (CIRC) model of Cooperative learning strategy. The study employed Classroom Action Research (CAR) design. The subjects of the study were three students of the fourth semester students of the English Department of Palangka Raya State Islamic College of 2007-2008 academic year. The result of the study showed that Cooperative learning strategy with Cooperative Integrated Reading and Composition (CIRC) model was effective in improving the studentsâ writing ability. It could be seen from the improvement of the studentsâ writing achievement. In the pretest before implementing the strategy, the average score of the studentsâ writing achievement was 4.00 in a 1.00 to 6.00 scale. Three students obtained âunevenâ level. However, after implementing Cooperative Integrated Reading and Composition (CIRC) model of Cooperative Learning strategy, the average score of the class in Cycle 1 increased slightly to 4.54. Only two students did not achieve the criteria of success.Â  Then, in Cycle 2, the average score of the class increased dramatically to 5.00, and all subjects achieved the criteria of success. Besides, the students enjoyed learning in writing class and they were highly motivated to join the cooperative class.Â